Glowing Sucker Octopus (Stauroteuthis syrtensis)‐Inspired Soft Robotic Gripper for Underwater Self‐Adaptive Grasping and Sensing (Adv. Sci. 17/2022). Issue 17 (13th June 2022) - Wu, Mingxin; Zheng, Xingwen; Liu, Ruosi; Hou, Ningzhe; Afridi, Waqar Hussain; Afridi, Rahdar Hussain; Guo, Xin; Wu, Jianing; Wang, Chen; Xie, Guangming
Abstract : Soft Robotic Gripper In article number 2104382 by Xingwen Zheng, Guangming Xie, and co‐workers, a soft gripper inspired by the glowing sucker octopus' enhanced grasping capability enabled by the umbrella‐shaped dorsal and ventral membrane between each arm is elaborated. The gripper features excellent abilities to suck and grasp objects with any shapes (planar and nonplanar) and dimensions. Furthermore, the gripper could generate tactile sensation for turbid water environment exploration.